FROM TRAUMA TO TRANSFORMATION: EXPLORING POSTTRAUMATIC GROWTH IN SEXUAL VIOLENCE SURVIVORS THROUGH A SCOPING REVIEW (Proceedings of the International Conference on Future of Women, 2025)
The incidence of sexual violence is increasing globally. In Indonesia, data from the NationalCommission on Violence against Women reveals that psychological and sexual violence are the two most prevalent forms of abuse, accounting for 37% and 28% of cases, respectively. These incidents have significant physical and psychological impacts on individuals. Despite this, survivors of sexual violence have the potential to experience positive transformation after trauma, known as posttraumatic growth (PTG). While research on PTG has progressed, a comprehensive mapping of trends and gaps in this area remains lacking. This study aims to map the literature on PTG among survivors of sexual violence, exploring research trends and methodologies employed. Utilizing a scoping review approach, a systematic literature search was conducted in September 2024 across major databases such as Scopus, PubMed, and ScienceDirect. Inclusion criteria required studies in which posttraumatic growth is the primary focus of measurement, specifically examine survivors of sexual violence. Utilize primary data, and explore posttraumatic growth beyond general discussions on growth-related topics. Articles were systematically screened based on relevance to the research question. The resultsidentified 19 relevant studies on PTG among survivors of sexual violence, focusing on psychological themes and employing diverse methodologies: 10 quantitative, 5 qualitative, and 3 mixed-methods studies. However, a significant gap exists in understanding how survivors translate their PTG experiences into concrete actions, such as self-empowerment, advocacy, or changes in interpersonal relationships. This study highlights the need for interventions based on PTG understanding, including advocacy programs and empowerment initiatives, to support the recovery and transformation of sexual violence survivors.
Keywords: posttraumatic growth; sexual violence; survivors; scoping review